Cannabis and cannabinoids as an alternative remedy in metabolic syndrome - Claudia Ali Montoya-Alatriste; Francisco Javier Alarcon-Aguilar (Universidade de São Paulo, 2022)
Abstract Metabolic syndrome (MetS), an epidemic defined as a group of interconnected physiological, biochemistry, clinical, and metabolic factors, directly increases the risk of cardiovascular disease, atherosclerosis, type 2 diabetes, and death. MetS therapy includes diet, physical exercise, and a poly-pharmacological intervention. Cannabis is mainly recognized for its recreational uses and has several medical applications for neurological diseases, due to its hypnotic, anxiolytic, antinociceptive, anti-inflammatory, and anticonvulsant activities. Although several clinical observations in Cannabis smokers suggest metabolic effects, its utility in metabolic disorders is unclear. This review aims to determine under what conditions Cannabis might be useful in the treatment of MetS. Cannabis contains 120 phytocannabinoids, of which Δ9-THC mediates its psychoactive effects. Cannabinoids exert biological effects through interactions with the endocannabinoid system, which modulates several physiologic and metabolic pathways through cannabinoid receptors (CB1/CB2). Signaling through both receptors inhibits neurotransmitter release. In general, endocannabinoid system stimulation in Cannabis smokers and Δ9-THC signaling through CB1 have been implicated in MetS development, obesity, and type 2 diabetes. In contrast, CB1 antagonists and non-psychotropic phytocannabinoids like cannabidiol reduce these effects through interactions with both cannabinoid and non-cannabinoid receptors. These pharmacological approaches represent a source of new therapeutic agents for MetS. However, more studies are necessary to support the therapeutic potential of Cannabis and cannabinoids in metabolic abnormalities.